Transforming adversity into an ally: A qualitative study of “feeding your demons” meditation - Ekman, Eve; Koenig, Christopher J.; Daubenmier, Jennifer; Dickson, Kate Greer; Simmons, Vanessa; Braun, Amy; Goldin, Philippe (Frontiers in Psychology, 2022)
Contemplative science has made great strides in empirically investigating meditation practices, including how mindfulness, compassion, loving-kindness, and mantra practices impact mental states, health, and well-being. However, other types of meditation practice that use imagery to transform distressing beliefs and emotions have been little explored. Using qualitative data analytic methods, we examined diary entries to two questions probing the effects of the Feeding Your Demons (FYD) meditation process, a secular adaptation of the traditional Tibetan Vajrayana meditation practice of Chöd (“Severance”). Written diary entries were collected immediately after each FYD meditation session during a randomized controlled study in which meditation practitioners were randomly assigned to either one month (up to 15 meditation sessions) of FYD practice or a waitlist (WL) control group. We used an Interpretive Phenomenological Analysis based approach to examine participant written responses to each question. Overall, participants reported a change in perspective related to increased empathy, specifically, the transformation of challenging emotions and experiences (which they typically perceived as "enemies" and “personal faults”) into personal insights, self-compassion, and acceptance.